Possibilities of using postnatal ultrasound screening of the uropoietic tract (Perioperaciina Medicina, 2021)
The article provides information on the possibilities of using postnatal ultrasound screening of the uropoietic tract illustrated by the results of using this method in the Slovak Republic. Its main task is to identify malformations of the uropoietic system that were not diagnosed during prenatal diagnosis. The most clinically significant malformations of the kidneys are associated with impaired urine flow (obstructive uropathy). Patients with these malformations often require surgical intervention in the neonatal period or in early childhood. Early diagnosis and timely correction of obstructive uropathy allows maintaining the normal functioning and morphological integrity of the kidneys, preventing the development of chronic kidney disease, improving the quality and life expectancy of patients. Thus, the costs of screening research are incommensurate with the consequences of an untimely diagnosed pathology and the treatment of complications such as chronic kidney disease, kidney failure, recurrent urinary tract infections (antibiotic therapy, hemodialysis, etc.).
Keywords: diagnosis; newborn; obstructive uropathy; postnatal period; screening; Slovakia; ultrasound